Estudo de Primeiros Princípios de Nanotubos de Carbono de Camada Dupla - Lima, Welber de Jesus Mendes (2008)
In this work, are studies the electronic and structural properties of the (8,0)@(13,0) e (6,0)@(13,0) double wall carbon nanotube of zig-zag type doped with atoms of the nitrogen and boron on the inner tube and outer tube. To studies these properties we used of the ab initio method employed of the density functional theory in the generalized gradient approximations. All simulations are make with the SIESTA code. Through of the results we observed that electronic properties, analysis via band structure, are changes with introduction of the impurity this systems. The results shown that nitrogen atom to act how a type-n doped and boron atoms act how a type-p doped. Through of the formation energy calculation we observed that (8,0)@(13,0) and (6,0)@(13,0) DWCNTs are energetic more favorable when is doped with nitrogen in inner tube and boron in outer tube.